Facilitators and Barriers of Engaging in Physical Exercises by Tertiary Students at one Campus of the University of Eswatini - Thulani Ricardo Nhlabatsi; Senzolumusa Constance Magongo (CV Media Inti Teknologi, 2026)
Background of study: Lack of physical exercise has significant influence on the rise of cases of non-communicable diseases (NCDs) among university students globally. University students` engagement in physical excercises tend to decline when compared to previous school years. The decline is also observed in Eswatini`s university students. This study, therefore, described the facilitators and barriers of engaging in physical exercises by tertiary students of one Campus of the University of Eswatini. Methods: A descriptive qualitative research design was employed to describe the facilitators and barriers of physical exercise of ten purposively sampled students. Data was collected through audio-recorded face-to-face interviews utilising a researcher developed interview guide. Data were analysed using thematic analysis of Colaizzi’s descriptive method of data analysis. Result: Four themes emerged from the study findings; 1) Students understanding of physical exercise, 2) Facilitators of physical exercise, 3) Barriers of physical excercise, 4) Strategies to improve physical exercise engagement. Conclusion: Students` physical exercise participation is characterised by facilitators and barriers. Therefore, students need practical support from the university in terms of provision of enough variety of training facilities and equipment within the campus, and time alocated for physical activities within the course of their learning.